Effectiveness of the Developed Micro Lesson in Dance Exercise (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2022)
In a world where new instructional processes are continuously being developed, crafting a micro lesson is one of them—testing its effectiveness and validity before implementation is part of the development process. This study examines the effectiveness of the developed micro lesson in dance exercises. The 270 Physical Education 1 students were identified as participants using a purposive sampling procedure. The result shows a significant change in the student's pre-test and post-test scores, indicating improved knowledge of dance exercises. The developed micro lesson is highly recommended to be used as a new method of teaching dance exercises in Physical Education subjects.